Effect of the consumption of a food based on fruits and natural additives in patients with cardiovascular risk - FRANCO LONDOÑO, Maria Camila; ISAZA, Adrián; POSADA, Gladys; MALDONADO CELIS, Maria Elena (Vitae, 2019)
Background: cardiovascular diseases (CVD), a group of disorders of the heart and blood vessels are the main cause of morbidity and mortality worldwide. Strategies for its prevention have been proposed, such as modifying life habits, including increasing the consumption of fruits and vegetables associated with the decrease in the probability of suffering CVD. Objective: to evaluate the effects of a base compote of guava (Psidium guajava) and passion fruit (Passiflora ligularis) on blood pressure and metabolic and inflammatory biomarkers in hypertensive type two diabetic patients. Methods: food characterization test (microbiological, proximal, sensorial, antioxidant activity and total phenols). The compote was administered for 21 days to 8 adults (30 to 65 years old); glycaemia, blood pressure, inflammatory markers, and BMI and waist circumference before and after the intervention were measured. Results: the sensory test showed: 66% acceptance and all attributes a value >3, indicating that it was well evaluated. The microbiological aspects comply with the safety for human consumption and nutritionally it stands out that the contribution of carbohydrates (12.3%) is adequate for these patients. The hydrophilic ORAC value was 98.570 μmol ET/g sample. In the patients at the end of the study, a statistically significant decrease in systolic blood pressure was observed (127 mmHg, p 0.041) and the pro-inflammatory markers TNFα, IL-1β and IL6 (31.9 pg/mL, p 0.012, 31.9 pg/mL, p 0.012, and 3.5 pg/mL, p 0.017 respectively) and glycaemia increase (157.5 mg/dL, p 0.036). Conclusions: the medium-term consumption of a compote based on guava, passion fruit, cinnamon and flaxseed oil improves systolic blood pressure and the proinflammatory markers TNFα, IL-1β and IL6 in diabetic and hypertensive patients.